IDENTIFICATION OF BACTERIAL CONTAMINATION ON MEDICAL SCISSORS BY BACTERIAL CULTURE METHOD IN THE AFTAP LABORATORY OF BHAKTI SETYA INDONESIA HEALTH COLTECH - widia rahmatullah; Danar Hermawan; Rudina Azimata R (STIKES Syedza Saintika Padang, 2025)
The room and equipment used for blood component processing must comply with the quality management system with one of the objectives to eliminate the risk of bacterial contamination in the blood supply unit. Medical scissors in the blood tapping process act as medical tools used to cut the blood bag tube after the blood volume obtained has been fulfilled. This study aims to determine and identify the presence of bacterial contamination in medical scissors in the blood tapping room (AFTAP) Poltekkes Bhakti Setya Indonesia Yogyakarta. This research method is True Experiment with The Posttest Only Design research design, namely the results of observations provide descriptive information. The samples taken were five medical scissors in the Aftap room Poltekkes Bhakti Setya Indonesia. The sampling method used is Quota sampling. The results of the study on the identification of bacterial contamination in medical scissors in the Blood Tapping Laboratory (AFTAP) Poltekkes Bhakti Setya Indonesia Yogyakarta found bacterial growth with details of 20 samples containing Gram Positive bacilli and cocci. The most commonly found bacteria are Gram Positive bacteria with a rod shape (Bacillus).